Tailoring the morphological features of hydrothermally synthesized mesoporous hydroxyapatite using polyphenols and phosphate sources - Zhou, H.; Yang, M.; Hou, S.; Ni, X.; Bi, Y.; Wang, W.; Kutty, M.G.; Yang, L. (Elsevier, 2017)
Hydroxyapatite (HA) is a well-known material for biomedical applications and its performance depends greatly on its morphological features. Therefore, preparation of mesoporous HA with high surface area and adsorption capacity is highly deserved. In this research, a hydrothermal approach to synthesize mesoporous HA without post-processing calcination step is presented. The possibility using different polyphenols to generate mesoporous HA as well as using different phosphate sources to tailor the morphological features of HA is investigated. The as-prepared mesoporous HA particles are characterized by XRD, FTIR, SEM, TEM, BET, and zeta potential. Besides, the impacts of HA morphological features on model drug Dox are also studied. It is expected the strong interaction between –OH of polyphenols and Ca2+ makes polyphenols molecules occupy the inner sites of growing HA particles. After the removal of polyphenols by hydrothermal treatment and ethanol extraction, the occupied sites are transformed into mesopores. The typical mesoporous HA generated in present work has a rod-like morphology with BET specific surface area of 106.6 m2/g and an average pore size of 14.4 nm.